Les trajectoires de conversion écologique face aux enjeux économiques et sociaux du « logement durable » en France - Philippe Hamman; Cécile Frank; Marie Mangold (VertigO)
This paper deals with the careers of ecological conversion of the lifestyles in France through the case of “green building” projects and focuses on two target groups : the first-time home-buyer and the over-sixties, in three different regions. In relation to the increasing real-estate business interested in sustainable housing, which frequently stresses a technical dimension closely linked with energy consumption and conservation, our research reveals a plurality of interconnected dynamics, according to a diversity of criteria (building materials, facilities, capacity for evolution, attractive features of the building, living environment, etc.). We can conclude that the contents of the “green housing” repertoire – as sustainable development policies more largely – involve more than a single frame and are not stabilized yet.